World of Earth Science - Lerner, K. Lee (The Gale Group, Inc, 2011)
This new title in Gale's World Of...Series is a comprehensive guide to the concepts, theories, discoveries, pioneers and issues relating to topics in earth science. World of Earth Science's encyclopedic approach offers approximately 650 entries in a convenient A-Z format, cross-reference headings and is written in easy to understand language. In addition to traditional subtopics in geology and meteorology, World of Earth Science also covers a substantial number of topics in astronomy. Special emphasis is also placed on current ethical, legal and social issues pertaining to the many topics covered. Includes a subject index, historical chronology, a list of sources consulted and 150-200 photographs and illustrations.